Modifications in magnetic anisotropy of M-type strontium hexaferrite crystals by swift heavy ion irradiation - Kaur, Balwinder; Bhat, Monita; Licci, F.; Kumar, Ravi; Kulkarni, S. D.; Joy, Pattayil Alias; Bamzai, K. K.; Kotru, P. N. (Journal of Magnetism and Magnetic Materials, 2006)
Using vibrating sample magnetometery (VSM) 50 MeV Li(3+) ion irradiation effects on magnetic properties of single crystals of SrGa(x)In(y)Fe(12-(x+y))O(19) (where x = 0, 5, 7, 9; y = 0, 0.8, 1.3, 1.0), are reported. The substitution of Ga and In in strontium hexaferrite crystals decreases the value of magnetization sharply, which is attributed to shifting of collinear magnetic order to a non-collinear one. Reduction of magnetization is also explained to be as a result of the occupation of the crystallographic sites of Fe(3+) by Ga(3+) and In(3+). The Li(3+) ion irradiation decreases the value of magnetization, irrespective of whether the crystals are Ga-In substituted or unsubstituted crystals of SrFe(12)O(19). The result is interpreted in terms of the occurrence of a paramagnetic doublet in crystals replacing magnetic sextuplet as a result of irradiation. Substitution of Ga-In in Strontium hexaferrite decreases the value of anisotropy constant. Irradiation with Li(3+) ions increases the values of anisotropy field for both substituted as well as unsubstituted crystals. Substitution with Ga-In also decreases the Curie temperature (T(c)) but the irradiation with Li(3+) ions does not affect the curie temperature of either Ga-In substituted or pure SrFe(12)O(19) crystals. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: anisotropy field; Curie temperature; irradiation; Magnetic anisotropy; Magnetization

Modification of crystal anisotropy and enhancement of magnetic moment of Co-doped SnO2 thin films annealed under magnetic field - Loya-Mancilla, Sagrario M.; Poddar, Pankaj; Das, Raja; Ponce, Hilda E. Esparza; Templeton-Olivares, Ivan L.; Solis-Canto, Oscar O.; Ornelas-Gutierrez, Carlos E.; Espinosa-Magaa, Francisco; Olive-Mendez, Sion F. (Nanoscale Research Letters, 2014)
Co-doped SnO2 thin films were grown by sputtering technique on SiO2/Si(001) substrates at room temperature, and then, thermal treatments with and without an applied magnetic field (H-TT) were performed in vacuum at 600 degrees C for 20 min. H-TT was applied parallel and perpendicular to the substrate surface. Magnetic M(H) measurements reveal the coexistence of a strong antiferromagnetic (AFM) signal and a ferromagnetic (FM) component. The AFM component has a N,el temperature higher than room temperature, the spin axis lies parallel to the substrate surface, and the highest magnetic moment m =7 mu(B)/Co at. is obtained when H-TT is applied parallel to the substrate surface. Our results show an enhancement of FM moment per Co+2 from 0.06 to 0.42 mu(B)/Co at. for the sample on which H-TT was applied perpendicular to the surface. The FM order is attributed to the coupling of Co+2 ions through electrons trapped at the site of oxygen vacancies, as described by the bound magnetic polaron model. Our results suggest that FM order is aligned along [101] direction of Co-doped SnO2 nanocrystals, which is proposed to be the easy magnetization axis.
Keywords: Antiferromagnetism; Crystal anisotropy; Diluted magnetic oxide; Ferromagnetism; Magnetic anisotropy; Magnetic moment; Spin axis; thin film

Study of magnetic entropy and heat capacity in ferrimagnetic Fe3Se4 nanorods - Sen Bishwas, Mousumi; Poddar, Pankaj (Journal Of Physics D-Applied Physics, 2016)
Change in the magnetic entropy and specific heat capacity in Fe3Se4 nanorods synthesized by a wet-chemical method in a broad temperature (215-340 K) and magnetic field range (0-60 k Oe) was studied. The isothermal magnetic entropy change (Delta S-M) is estimated by an indirect method from the isothermal magnetization curves measured in this temperature range. S-M(max) of -46 x 10(-2) J kg(-1).K-1 was obtained at similar to 317 K when the field was changed from 0 to 60 kOe. The maximum in the isothermal magnetic entropy change (Delta S-M) is observed in close proximity to TC (similar to 323 K), which is linked to the order-disorder transition. The nature of this transition was analyzed by universal curve behavior. The temperature and magnetic field dependence of specific heat capacity was studied and analyzed to estimate the adiabatic temperature change (Delta T-ad). The magnetic entropy change of Fe3Se4 nanoparticles is found to be comparable with similar ferrite and manganite nanoparticle systems and a broad operating temperature window of similar to 30 K was observed around room temperature.
Keywords: heat capacity; iron selenide; Magnetic anisotropy; magnetic entropy; order-disorder phase transition